Social Labeling, Power, and Deviancy Amplification: Community Stigmatization of Migrant Residents in Adultery Cases in Banda Aceh - Mujtahid, Mujtahid; Sodiqin, Ali; Ichwan, Moch. Nur (Institut Agama Islam Negeri (IAIN) Pontianak, 2025)
Existing research on social labeling in adultery (zinā) cases in Aceh remains limited, particularly in exploring how local power dynamics shape processes of stigmatization. This article examines how the social labeling of migrant residents (ureung tamong) accused of zinā operates as a mechanism of social control that reinforces the dominance of local residents (asoe lhok), while media exposure intensifies stigma through deviancy amplification. Employing a legal anthropological approach, the article is based on three months of fieldwork in Banda Aceh, involving participant observation, in-depth interviews with ten key informants—including village authorities, community leaders, law enforcement officers, and local residents—and analysis of relevant online and social media content. The findings reveal that social labeling in zinā cases is driven not only by religious and customary norms but also by underlying community power structures, rendering ureung tamong significantly more vulnerable to public exposure and social sanctions than asoe lhok. Additionally, digital media exacerbates the amplification of deviance, resulting in prolonged social exclusion of individuals who have already faced customary or formal legal punishment. The persistence of digital records further obstructs their reintegration into society. This article contends that social labeling functions not merely as a tool of moral regulation but also as a strategy for maintaining the dominance of powerful groups within the community. It concludes by calling for more inclusive media practices and legal policies to prevent the prolonged social and psychological marginalization of individuals in zinā cases who have fulfilled their legal obligations. [Penelitian mengenai pelabelan sosial dalam kasus perzinaan di Aceh masih terbatas, khususnya dalam menelaah bagaimana dinamika kekuasaan lokal membentuk proses stigmatisasi. Artikel ini mengkaji bagaimana pelabelan sosial terhadap pendatang (ureung tamong) yang diduga melakukan zina berfungsi sebagai mekanisme kontrol sosial yang memperkuat dominasi penduduk lokal (asoe lhok), serta bagaimana eksposur media memperparah stigma melalui amplifikasi penyimpangan. Dengan menggunakan pendekatan antropologi hukum, artikel ini didasarkan pada kerja lapangan selama tiga bulan di Banda Aceh, yang meliputi observasi partisipatif, wawancara mendalam dengan sepuluh informan kunci—terdiri dari aparatur desa, tokoh masyarakat, aparat penegak hukum, dan warga lokal—serta analisis terhadap konten media daring dan media sosial yang relevan. Temuan menunjukkan bahwa pelabelan sosial dalam kasus zina tidak semata-mata dipengaruhi oleh norma agama dan adat, tetapi juga oleh struktur kekuasaan di dalam komunitas, sehingga ureung tamong jauh lebih rentan terhadap eksposur publik dan sanksi sosial dibandingkan asoe lhok. Selain itu, media digital memperburuk amplifikasi penyimpangan, yang berujung pada pengucilan sosial berkepanjangan terhadap individu yang telah menjalani sanksi adat maupun hukum formal. Keberadaan jejak digital yang terus bertahan semakin menghambat proses reintegrasi sosial mereka. Artikel ini menegaskan bahwa pelabelan sosial berfungsi tidak hanya sebagai alat regulasi moral, tetapi juga sebagai strategi untuk mempertahankan dominasi kelompok yang berkuasa di dalam komunitas. Oleh karena itu, penelitian ini merekomendasikan adanya kebijakan media dan hukum yang lebih inklusif guna mencegah marginalisasi sosial dan psikologis yang berkelanjutan terhadap individu dalam kasus zina yang telah menjalani sanksinya.]